2016
DOI: 10.4314/sajas.v45i5.7
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of organic matter digestibility, metabolizable energy, phenolic compounds and antioxidant activity of stems and seeds of the <i>Juncus acutus</i> plant in ruminant nutrition

Abstract: The objectives of the present study were to determine the organic matter digestibility (OMD), metabolizable energy (ME), antioxidant activity and total phenolic and flavonoid concentrations of stems and seeds of Juncus acutus. Stem and seed samples were collected from Hamsiloz Bay in Sinop, Turkey, and the proximate analysis was carried on them. The OMD percentage and ME values of the samples were estimated from gas measured by the in vitro gas production method. Phenolic and flavonoid concentrations and total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
2
4
1
Order By: Relevance
“…Te lowest IVOMD was recorded from mutica (40.66) without fertilizer at red soil. In line with the current study [60] reported that IVOMD diferences were noted by brachiaria species cultivars. Te highest IVOMD was obtained from hybrid Mulato-II (50.9), hybrid Mulato (49.4), and marandu (43.7) at 90 days of harvesting age.…”
Section: In Vitro Dry Matter and Organic Matter Digestibilitysupporting
confidence: 92%
See 1 more Smart Citation
“…Te lowest IVOMD was recorded from mutica (40.66) without fertilizer at red soil. In line with the current study [60] reported that IVOMD diferences were noted by brachiaria species cultivars. Te highest IVOMD was obtained from hybrid Mulato-II (50.9), hybrid Mulato (49.4), and marandu (43.7) at 90 days of harvesting age.…”
Section: In Vitro Dry Matter and Organic Matter Digestibilitysupporting
confidence: 92%
“…12 MJ/kg [60]. Hereafter, according to this classifcation, all Brachiaria cultivars grown in both soil types and fertilizer application in the current study was classifed as low energy feed content that are below the minimum maintenance energy requirement of livestock production [60] of course it explains the feature of tropical forage plants.…”
Section: In Vitro Dry Matter and Organic Matter Digestibilitymentioning
confidence: 99%
“…The total polyphenol and total lavonoids contents of our extracts were higher than those found in other studies of Juncus acutus (Erdem et al, 2016) and Juncus effuses (Li et al, 2013).…”
Section: Total Lavonoid Contentcontrasting
confidence: 91%
“…The test is based on the reduction of Mo(VI) to Mo(V) by the analyte of the sample and subsequent formation of a green Mo(V) phosphate complex at acid pH. The reduction capacities of Juncus acutus extracts were determined by reference to the calibration curve of vitamin C.The most important reducing power was noted for the ultrasound ethyl Our results showed greater antioxidant activity than those found in other studies performed on Juncus Bufonius (El-Gawad et al, 2015), Juncus acutus (Erdem et al, 2016). It is also noted that the highest total polyphenol content as well as total lavonoids content and the most important antioxidant activity was observed in the ethyl acetate extract by ultrasound.…”
Section: Phosphomolybdate Testsupporting
confidence: 45%
“…At the moment, a considerable number of scientifically-practical researches aimed at studying polyphenol component of numerous products of economic activity, such as wine [1], some agricultural products [2,3], and herbs, among which lists the oat, Avena Sativa, in its various natural and synthetic forms, are known. Polyphenols of the vegetative nature are represented by a variety of forms that potentially anticipates a wide range of non-specific and specific biological activity, and actualizes its further research and application in the medical practice [4,5].…”
Section: Introductionmentioning
confidence: 99%